RELEVANSI QIYAS DALAM STRUKTUR HUKUM ISLAM - Ahmad Fauzi (MAQASHID Jurnal Hukum Islam, 2022)
Al-Qur'an, Hadith, Ijma, and Qiyas are the four main texts of Islamic law accepted by the scholars. On the other hand, Islamic law that is often cited by religious figures other than those listed above is istihsan, maslahah mursalah, istishab, "uruf, madzhab as-Shahabi, and syar'u man qablana. The existence and blasphemy of qiyas as a first step in establishing law still raises several problems and heated debates in the short term. Not all of the Qur'an, Sunnah, or Ijma' acknowledge the status of qiys as a valid legal proposition. The author tries his best in this case to describe a little about the views of the Syafi'iyyah jumhur ulama' towards the position of qiyas as one of the methods of establishing law in Islam. Therefore, without exception, those who use common sense in Islamic law will also be able to grow the spirit of Islam itself. Apart from using the available databases of books and nomenclature of Islamic law, this method of library research also using descriptive analysis.Based on the analysis, it was found that the level of relevance of qiyas as a method has been h has increased significantly since this writing was written, especially considering the region and spread of Islam which is basically cross-country, cross-national and cross-cultural. Qiyas remains a necessity for Muslims, which shows that not everyone is capable of doing istinbaht or drawing conclusions about Islamic law.